"What for? I'll be 18 soon and getting out of here": Future orientation among immigrant at-risk youth in Israel. (September 2020) - Klein, Shaked; Shoshana, Avihu
Highlights: The future orientation of at-risk immigrant youth is examined phenomenologically. Participants were recent low-SES immigrants to Israel. The youth reported ambiguity, uncertainty, and liminality regarding their stay in Israel. The youth's desire for "normality, " expressed in their desire for a stable income. The youth noted that their significant adults do not speak with them about their future. Future orientations are discussed in the context of privilege and structural inequality. Abstract: This article examines the phenomenology of the future orientation of at-risk youth who immigrated to Israel over the past two years from low socioeconomic status communities of Former Soviet Union countries. These youth emigrated from these communities with their family to one of the poorest neighborhoods in a city in northern Israel. Two major questions reside at the foundation of our study: (1) How do these at-risk youth experience their contemporary life in the host country? (2) What is the future orientation of these at-risk youth? To examine these research questions, we conducted in-depth interviews with 16 boys and girls aged 12–17, studying in grades 7–12. The main research findings reveal that all respondents see Israel as a transit station, aspire to emigrate to other countries, insist on preserving their Russian culture (including refusal to learn Hebrew), and maintain their Russian identity through transnationalism, facilitated by technology. In light of this, the youth expressed a sense of high temporality and ambiguity regarding their remaining in Israel and their dependence on their parents' decisions regarding the possibility of further emigration. Moreover, our findings reveal the youth's desire for "normality, " which is expressed primarily in the desire for employment that enables a stable income. Most youths could not state what that job would be, where they would like to work in the future, and in what profession. Issues discussed include the ramifications of time and temporality (through the concept of liminality and the experience of waiting) in the life characteristics of the youth, the impact of these characteristics on their future orientation, and their contribution to social exclusion and social inequality.